2019
DOI: 10.3390/ijms20092369
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Kombucha Tea in Rodent Model of Nonalcoholic Fatty Liver Disease/Nonalcoholic Steatohepatitis

Abstract: Kombucha tea (KT) has emerged as a substance that protects the liver from damage; however, its mechanisms of action on the fatty liver remain unclear. Therefore, we investigated the potential role of KT and its underlying mechanisms on nonalcoholic fatty liver disease (NAFLD). db/db mice that were fed methionine/choline-deficient (MCD) diets for seven weeks were treated for vehicle (M + V) or KT (M + K) and fed with MCD for four additional weeks. Histomorphological injury and increased levels of liver enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 69 publications
0
12
0
3
Order By: Relevance
“…Studies have shown that the biologically active compounds in green tea had antioxidant, hypolipidemic, and anti-inflammatory effects, thereby reducing the risk of NAFLD (26,27). Another tea, Kombucha KT, protected the liver cells from inflammation and fibrosis, which helped restore liver function in NAFLD mice (28). Our research showed a new drink of Citrus maxima cv.…”
Section: Discussionmentioning
confidence: 62%
“…Studies have shown that the biologically active compounds in green tea had antioxidant, hypolipidemic, and anti-inflammatory effects, thereby reducing the risk of NAFLD (26,27). Another tea, Kombucha KT, protected the liver cells from inflammation and fibrosis, which helped restore liver function in NAFLD mice (28). Our research showed a new drink of Citrus maxima cv.…”
Section: Discussionmentioning
confidence: 62%
“…In a biological study with mice Lee et al. (2019) induced liver steatosis in animals using a diet low in methionine and applied the supplementation of kombucha fermented from black tea, which was able to prevent vacuolization when compared to the group that did not receive this supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the hepaprotective efficacy of kombucha has been studied by liver toxicity markers' assessment, such as serum glutamic pyruvate transaminase, assessing the antioxidant enzymes, like superoxide dismutase and catalase, and various levels of creatinine and urea in the liver tissue [25]. Lee and collaborators [33] were able to show the protective characteristic of Kombucha in insulin-resistant mice, improving liver The literature also highlights the high antioxidant potential of Kombucha [21,24,25]. This antioxidant property depends on three important factors: the type and composition of the tea infusion, the SCOBY, and the fermentation process.…”
Section: Kombucha: Concept and Health Benefitsmentioning
confidence: 99%